GENERAL CONTACTS: JOURNALS, MAGAZINES, AND NEWS SOURCES - Schlesinger, Lynn; Taub, Diane (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
List of resource contacts by websites on disability issues.